Experimental study on a wide-band piezoelectric energy harvester with rotating beams vibrating in perpendicular directions. Issue 168 (2nd January 2016) - Yang, L. J.; Zhang, H. F.
ABSTRACT: We present here a new design for a wide-band piezoelectric energy harvester. Our system consists of two mutually perpendicular cantilever beams with attached PZT (lead zirconate titanate) patches. Traditional piezoelectric energy harvesters can only generate a single resonance peak and therefore they are limited by a narrow band and low power output. In this paper, by using two piezoelectric cantilever beams aligned in a mutually perpendicular direction, two resonance peaks are observed. Additionally, by adjusting the rotation angle of these beams, the operational frequency bandwidth has been enlarged by 70%–100%. Therefore, our new piezoelectric energy harvester has the potential to harvest energy in a wider frequency range for practical applications with variable frequency sources.